COMPARISON OF PERIODONTAL HEALTH STATUS OF SMOKERS VERSUS NON-SMOKERS - Jogezai, Ursala; Maxood, Anser; Khan, Noosheen Asim (Journal of Ayub Medical College Abbottabad, 2013)
Background: This study aims to compare the periodontal health status of current smokers versus non-smokers. The study was carried out in the Dental department, Pakistan Institute of Medical Sciences (PIMS) between May 2009 and June 2010. A total of 280 male subjects, married, over the age of 18 were selected to take part in the study and their periodontal health was assessed by presence of calculus, bleeding on probing and pocket depth greater than four millimetres. Methods: Patients including smokers and non smokers were selected on the basis of the inclusion and exclusion criteria. Subjects were clinically evaluated by using a specially designed CPITN probe which was used to measure pocket depths in the mouth. The mouth was divided into six sextants. The other variables examined included bleeding on probing and presence of calculus. The data was subsequently analyzed using the SPSS statistical software programme. The statistical significance level was set at 5%. Results: There was decreased incidence of bleeding on probing (31.7%) in smokers than non-smokers (53.5%) however, there was an increased incidence of calculus formation among smokers (89.4%) compared to the subjects who did not smoke (69.6%). There was a significant difference between the overall mean pocket depth in smokers (3.7±1.4) and non-smokers (3.0±1.1). All of the above differences were found to be statistically significant. Conclusion: There was a marked association between cigarette smoking and periodontal disease. Keywords: Periodontal ligament, Periodontal disease, Calculus, pocket depth, Smoking